New species and new records of sea spiders (Arthropoda: Pycnogonida) from deep waters in Western Australia - Arango, Claudia P. (Zootaxa, 2009)
New species and new records of sea spiders for Australia were collected by the RV Southern Surveyor from deep waters off Western Australia during November and December 2005. This study reports fifty-three specimens from five families: Colossendeidae is represented by three species, one of them new to science, Hedgpethia calva n. sp.; there are eight species of the Callipallenidae, including Pseudopallene difficile n. sp.; two species of the Pallenopsidae, one of them a new record for Australia, and a single species of the Nymphonidae, Nymphon rottnesti. Ammotheids are represented by a juvenile of a Cilunculus and two new species, Paranymphon bifilarium n. sp. and Tanystylum zuytdorpi n. sp.